Convergence of neurodegeneration and the arts: a conversation between researchers about stigma, co-creativity, and transformation - Naila Kuhlmann; Pia Kontos; Maria Bee Christensen-Strynø; Stefanie Blain-Moraes (Research Involvement and Engagement)
Abstract Parkinson’s disease and dementia are highly stigmatized, creating social exclusion and inequality by depriving persons living with these conditions of their human rights and threatening their health, well-being, and quality of life. Challenging the stigma associated with these conditions is a key public health priority across national and international settings, and arts-based approaches are advocated to achieve this. We are researchers who use artistic and creative media including documentary films, research-based theatre, dance, circus and graphic narrative to challenge dominant and oppressive cultural and social norms, and to imagine and affect inclusive, compassionate, and socially-just approaches to supporting people to live well with neurodegenerative conditions like dementia and Parkinson’s. This includes fostering opportunities for co-creative engagement with people living with these conditions, to promote their inclusion as co-creators rather than subjects in research initiatives. In this conversation-style article, we draw on our qualitative research and experiential knowledge to reflect on the challenges and opportunities regarding arts-based research with people living with Parkinson’s disease or dementia. We share examples from our own work, across a range of artistic approaches, to illustrate the transformative potential of the arts to affect social change and to bring to light the tensions that arise in co-creative processes. Through this conversation, we hope to inspire and equip others to draw on the power and complexities of arts-based approaches for the co-production of knowledge to transform societal representation of neurological conditions and to foster human flourishing.